التخطيط الاستراتيجي كألية للنهوض بالسياحة في الجزائر - بن جاب الله, نبيلة (University of Eloued جامعة الوادي, 2015)
إن السياحة أصبحت صناعة مستديمة منتجة وفعالة ذات تأثير إيجابي كبير على جميع جوانب الاقتصاد وركيزة مهمة لتحقيق أهداف التنمية الشاملة والمستديمة. ويعد تحقيق التنمية الموضوع الأساس المسيطر لعدد من دول العالم لمواجهة مشكلاتها الاقتصادية في مجال السياحة بما يحتم عليها اقتناص الفرص وسد الثغرات وذلك بالاستثمار في مواردها الطبيعية التي تخدم النشاط السياحي على وجه الخصوص من أجل النمو السريع لتحقيق المكاسب والمنافع. إذ يقوم المنتج السياحي أساسا على ثروات غير مادية بالدرجة الأساس مثل المناخ المعتدل يشجع زيارة المعالم الاثرية والتاريخية والدينية ومناطق الجذب الطبيعي كالشلالات والينابيع، وقد ازداد الاهتمام من قبل المهتمين بالجانب السياحي باعتماد استراتيجيات التميز لتحقيق الأهداف الاقتصادية في المحافظة على البيئة واستثمار الطبيعة لتقديم منتجات سياحية مستديمة بما يخدم الاقتصاد من جهة والسائح والحركة السياحية من جهة أخرى. واستنادا عليه حظي قطاع السياحة في الجزائر في السنوات الأخيرة باهتمام صانعي القرار تجسد في وضع آليات لتفعيل دور السياحة وذلك بوضع خطط لتامين هيكلة وإرشادات أساسية لتخطيط سياحي شامل. واستنادا عليه تأتي هذه الورقة البحثية لمناقشة كيفية تجسيد التخطيط الاستراتيجي في قطاع السياحة انطلاقا مما تزخر به الجزائر من إمكانات في هذا المجال. Strategic planning as a mechanism for the promotion of tourism in Algeria Abstract The tourism industry has become a sustainable productive and effective with a significant positive impact on all aspects of the economy and an important pillar for achieving the goals of comprehensive and sustainable development . The development theme basically controlling for a number of countries in the world to face the economic problems in the field of tourism , including of having to capture the hypothesis and and fill in the gaps and investing in natural resources that serve the tourist activity in particular for the rapid growth of the gains and benefits. As a tourism product mainly on the wealth of non-material class basis , such as mild climate encourages sightseeing archaeological , historical and religious attractions, natural waterfalls and springs has been increased interest by the interested side tourist Batmada strategies excellence to achieve the economic goals of preserving the environment and investment nature to provide tourism products sustainable , including serve the economy on the one hand and the tourist and the tourist movement on the other. And it was based on the tourism sector in Algeria in recent years, with interest embodied in the decision-makers to develop mechanisms to activate the role of tourism and it plans to restructure and secure the basic guidance for planning a comprehensive tourist . Based upon this paper come to discuss how the embodiment of strategic planning in the tourism sector, which based on the wealth of the potential of Algeria in this area
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: التخطيط - التخطيط الاستراتيجي - السياحة